ANALISIS USAHATANI BROKOLI (Brassica oleracea L) DAN PEMASARANNYA DI DESA SUMBER URIP KECAMATAN SELUPU REJANG KABUPATEN REJANG LEBONG - Sarwai, Bembi Akbar; Sriyoto, Sriyoto; Yuliarti, Ellys (Jurnal AGRISEP, 2016)
This research was conducted with the purpose to: (1) Determine the system of financing farming Broccoli, (2) Calculate farm income of Broccoli, (3) Investigate marketing channels of Broccoli, Calculate its marketing margin and knowing marketing efficiency Broccoli in Sumber Urip village Sub-District Selupu Rejang District of Rejang Lebong. Respondents of Broccoli Farmers are censused 45 Farmers while marketing agencies are determined with Snowball Sampling, total respondent marketing agencies are 25 respondents. The result of this research indicated that the average farmers in the Sumber Urip village their own capital resources obtained from previous farming Broccoli. The averaged  income of Broccoli as Rp 5.850.717/Ut/MT. The marketing analysis indicated that the only Broccoli marketing channel in Sumber Urip village was through Farmers à Countryside à Wholeseller à Town   Wholeseller à Retailers à Final Consumers. The marketing margin analysis showed that the total marketing margin Broccoli is Rp 10.942/Kg. Broccoli Marketing efficiency analysis results in Sumber Urip shows that every marketing agencies Broccoli studied all efficient it can be seen from the value criteria Countryside Wholeseller is 1.28, Districts Traders 5.52, Town Wholeseller is 1,83 and Retailers 19,21.